2006 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--318
|View full text |Cite
|
Sign up to set email alerts
|

Converging Diverging Approach To Design In The Sophomore Engineering Clinic

Abstract: and has been teaching writing to engineering students for over ten years and has been a part of Rowan's Sophomore Clinic team since 1998. She received her Ph.D. from the University of Wisconsin-Milwaukee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…At best, they have a framework to which they can map their own process. Faculty teaching Sophomore Engineering Clinic in the past had observed that students had difficulty successfully navigating the design process 13,14 . While students were successful in analyzing a final truss design and building artifacts, there was little evidence of a well thought-out design process.…”
Section: Design Philosophymentioning
confidence: 99%
See 2 more Smart Citations
“…At best, they have a framework to which they can map their own process. Faculty teaching Sophomore Engineering Clinic in the past had observed that students had difficulty successfully navigating the design process 13,14 . While students were successful in analyzing a final truss design and building artifacts, there was little evidence of a well thought-out design process.…”
Section: Design Philosophymentioning
confidence: 99%
“…In the fall semester (SEC I), the students are split into two different lab sections, each with approximately 60 students. Student teams work on a four-week rocket design project 14 , followed by a ten-week crane design project 13 . In the spring semester (SEC II), all 120 students are in a single design lab section, but are allowed to choose between two distinct projects.…”
Section: Design Philosophymentioning
confidence: 99%
See 1 more Smart Citation